Risk factors for persistent elevation of perioperative lactate levels in gastric cancer surgery - Gulmez, Selcuk; Uzun, Orhan; Senger, Aziz Serkan; Keklikkiran, Zehra Zeynep; Bozkurt, Hilmi; Omeroglu, Sinan; Bozdag, Emre; Avan, Deniz; Polat, Erdal; Duman, Mustafa (Asian Journal of Medical Sciences, 2020)
Background: The impact of high-risk surgery on tissue perfusion can be indirectly assessed by measuring lactate levels during surgery and intensive care unit (ICU) stay. While consistently high values are associated with poor prognosis, transient elevations do not mean poor clinical outcomes. Therefore, intraoperative and early postoperative blood lactate monitoring is essential for cancer patients. Aims and Objective: This study aimed to determine the risk factors of persistently elevated lactate levels in the intraoperative and postoperative period in patients with elective gastric cancer surgery. Materials and Methods: We retrospectively enrolled 293 patients who underwent curative resection for gastric cancer. Lactate values of all patients were examined during surgery and ICU-stay at 3rd, 6th, 12th, and 18th hours. All lactate values above 2 mmol/L were considered elevated. The patients were divided into two groups as those with perioperative persistently increased lactate levels and those without. Results: Of the 293 patients, 60 (20.5%) had higher lactate levels in the perioperative period. According to multivariate logistic regression analysis, the operative time had the highest significance rate (p = 0.020) out of two significant variables, followed by the BMI ≥ 30 kg/m2 (p = 0.048). Besides, patients with perioperative hyperlactatemia had prolonged hospital stays (p = 0.034). Conclusions: Operative time and obesity (BMI ≥ 30 kg/m2) were independent risk factors for persistent lactate elevation in the perioperative period. Also, perioperative hyperlactatemia extended the length of hospital stay.